1999
DOI: 10.2114/jpa.18.233
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Regulation during Water Immersion.

Abstract: Abstract. Head-out water immersion at thermoneutral temperature (34-35 C) increases cardiac output for a given O2 consumption, leading to a relative hyperperfusion of peripheral tissues. To determine if subjects immersed in water at a colder temperature show similar responses and to explore the significance of the hyperperfusion, cardiovascular functions were investigated (impedance cardiography) on 10 men at rest and while performing exercise on a leg cycle ergometer (DM = ~95 W·m -2 ) in air and in water at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
21

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 34 publications
1
23
0
21
Order By: Relevance
“…Hornery et al (2005) also observed a trend towards lower _ VO 2 and HR values following V during a constant cycling exercise at 75% _ VO 2max in a similar environment (21°C vs. 20°C in the present study). Lower relative changes in exercise-induced responses, i.e., Ex1 to Ex2 for submaximal HR and _ VO 2 values after V exposition, may suggest a cold-related peripheral vasoconstriction and a greater central blood volume; often reported to enhance O 2 perfusion to active muscles, removal of waste substances, and assist exercise tolerance (Hessemer et al 1984;Hornery et al 2005;Park et al 1999;Vaile et al 2008). However, the sudden and greater change in T skin when entering water probably caused more severe vasoconstriction than V, along with potential increases in catecholamine release (Kozyreva et al 1999) and BP (Janský et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hornery et al (2005) also observed a trend towards lower _ VO 2 and HR values following V during a constant cycling exercise at 75% _ VO 2max in a similar environment (21°C vs. 20°C in the present study). Lower relative changes in exercise-induced responses, i.e., Ex1 to Ex2 for submaximal HR and _ VO 2 values after V exposition, may suggest a cold-related peripheral vasoconstriction and a greater central blood volume; often reported to enhance O 2 perfusion to active muscles, removal of waste substances, and assist exercise tolerance (Hessemer et al 1984;Hornery et al 2005;Park et al 1999;Vaile et al 2008). However, the sudden and greater change in T skin when entering water probably caused more severe vasoconstriction than V, along with potential increases in catecholamine release (Kozyreva et al 1999) and BP (Janský et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to convective heat loss, the effect of hydrostatic pressure during water immersion techniques may be an important aspect of the effectiveness of water immersion interventions (Park et al 1999). The pressure applied to the body during water immersion may cause displacement of fluids from the extremities, thus increasing the central blood volume, and leading to an increased stroke volume during immersion (Bonde-Petersen et al 1992;Gabrielsen et al 2002;Stocks et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANP acts as a vasodilator via endothelial cells and promotes baroreflex-mediated activation. The pronounced sympatholytic effect of ANP leads to a reduced vasoconstriction in W compared to L. 17 The sympathicolysis corresponds well with lowered plasma noradrenalin concentrations. 33,34 Furthermore, larger ANP blood concentrations constrain the RAA-system by reducing the release of renine and aldosterone.…”
Section: Discussionmentioning
confidence: 76%
“…The physical properties of water change hemodynamic and metabolic responses: stroke volume increases by 30-50% and cardiac output at a given work load also increases about 25% through the Frank Starling mechanism. 15,16 From increased cardiac output as a result of increased cardiac filling pressure and lowered total peripheral resistance 17 it can be assumed that O 2 extraction in working muscles is more efficient in W than on L. However at present the effect is discussed controversial. Blood flow to oxidative muscles can also be affected if muscle pump generates a greater pressure gradient across the capillary bed and increases blood flow.…”
Section: Introductionmentioning
confidence: 99%